SEJARAH RINGKAS PERKEMBANGAN ILMU BERKAITAN PERUBATAN TRANSFUSI DAN SUMBANGAN IBN NAFIS SEBELUM WILLIAM HARVEY, 1628 (A Brief Histroy of Development of Transfusion Medicine Related Knowledge and Ibn Nafis’s Contribution Prior to William Harvey, 1628) - Zabidi, Muhammad Azrul (Journal of Al-Tamaddun, 2018)
This study discusses the brief histrorical contributions of an Arab-Muslim physician scholar named Ala Ad-Din Abu Al-Hasan Ali Ibn Hazm Al-Qarshi or Ibn Nafis to the development of transfusion medicine science that were subsequently further advanced by numerous of Western medical scholars particularly after William Harvey published his Motu Cordis (1628). Between year 1600-1900 witnessed great discoveries related to human blood transfusion despite there were several undesirable consequences due to incompatible reactions including loss of lives. Such incidence led to more than 100 years of moratarium on its practice across Europe due to limited knowledge on its safety. This study utilises library study method to analyse various primary and secondary sources. The findings of this study came across several name of Western scholars, but William Harvey was the most prominent scholar and regarded as the Father of Human Blood Circulation System for describing human cardiovascular system. Nonetheless, it was little-known that 300 years before Harvey, Ibn Nafis was first to describe human blood circulation system in his writting, Syarah Al-Tashreeh al Qanun (1260). Ibn Nafis unravelled that human blood firstly circulated from heart through respiratory system before returned back to heart, denying the myth of ‘invisible pores’ in cardiac interventricular septum. His contribution was further advanced by Harvey leading to numerous of consequent discoveries.